DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management. (May 2023) - Carreiro, Ana Rita; Ramos, Jaime A.; Mata, Vanessa A.; Almeida, Nathalie M.; Rodrigues, Isabel; dos Santos, Ivo; Matos, Diana M.; Araújo, Pedro M.; Militão, Teresa; González-Sólis, Jacob; Paiva, Vitor H.; Lopes, Ricardo Jorge
Abstract: Overfishing has been drastically changing food webs in marine ecosystems, and it is pivotal to quantify these changes at the ecosystem level. This is especially important for ecosystems with a high diversity of top predators such as the Eastern Atlantic marine region. In this work we used high-throughput sequencing methods to describe the diet of the two most abundant tuna species, the Skipjack tuna ( Katsuwonus pelamis ) and the Yellowfin tuna ( Thunnus albacares ), highly targeted by fisheries off west Africa. We also explored prey diversity overlap between these tuna species and the seabird species breeding in Cabo Verde that are most likely to share prey preferences and suffer from bycatch, the Brown booby ( Sula leucogaster ) and Cape Verde shearwater ( Calonectris edwardsii ). Overall, the diet of both tuna species was more diverse than that of seabirds. Skipjack tuna diet was dominated by prey from lower trophic levels, such as krill, anchovies, and siphonophores, while the Yellowfin tuna diet was mainly based on epipelagic fish such as flying and halfbeak fishes. Some of the most abundant prey families detected in the Yellowfin tuna diet were shared with both seabird species, resulting in a high prey diversity overlap between this tuna species and seabirds These results have implications for the management of tuna fisheries in the Eastern Tropical Atlantic, because a large decrease of both tuna species might have cascading effects on both primary and secondary consumer levels, and the decrease of these underwater predators may have implications on the viability of tropical seabird populations. Highlights: DNA metabarcoding assess diet of tuna and seabirds of Eastern Atlantic Ocean. Skipjack tuna diet was dominated by prey from lower trophic levels. Significant diet overlap between Brown booby and Yellowfin tuna. Results have implications for the management of fisheries in this region.